Innovations in the Science and Practice of Decision Analysis: The Role ofManagement Science - Dyer, James S.; Smith, James E. (Management Science, 2021)
In this paper, we reflect on research in decision analysis that has appeared in Management Science and its impact on decision analysis practice and applications. We consider professional applications of decision analysis in business and government settings as well as everyday conversational applications. This paper was accepted by David Simchi-Levi, Special Section of Management Science: 65th Anniversary.